Photopyroelectric spectrum of MNO2 Doped Bi2O3 - TiO2 - ZnO ceramic combination - Rizwan, Zahid; Zakaria, Azmi; Mat Yunus, Wan Mahmood; Hashim, Mansor; Shaari, Abdul Halim (Universiti Putra Malaysia Press, 2008)
Photopyroelectric spectroscopy is used to study the energy band-gap of the ceramic (ZnO 0.25 Bi2O3 +0.25 TiO2 + x MnO2), x = 0 - 1.3 mol%, sintered at isothermal temperature 1190 and 1270°C for 2 hours in air. The wavelength of incident light, modulated at 9 Hz, is kept in the range of 300 to 800 nm and the photopyroelectric spectrum with reference to the doping level is discussed. The energy band-gap is estimated from the plot (phv)2 vs hv and is 2.80 eV for the samples without MnO2 at both sintering temperatures. It decreases to 2.08 eV with a further increase of MnO2. The phase constitution is determined by XRD analysis. Microstructure and compositional analysis of the selected areas are analyzed using SEM and EDX. The maximum relative density, 91.4 %, and the grain size, 47 µm, were observed in this ceramics combination.